PENGARUH STRES KERJA, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT TELKOM AKSES SENTRAL TELEPON OTOMAT (STO) 1 CENTRUM CABANG BANJARMASIN - Ruslinda Agustina; - Soedjatmiko; Etty Rastika (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, This study aims to prove empirically the effect of work stress, motivation and compensation on the performance of employees of PT Telkom Telephone Central Phone Access (STO) 1 Centrum Banjarmasin Branch. The sample of this study amounted to 40 employees who were responded to with the help of the SPSS version 16.00 for windows software statistical test tool. The results of this study indicate H1 0.396 and H3 0.160 which means that the value is greater than 0.05, namely work stress and rejected compensation does not affect employee performance. Whereas, the results of the H2 study show 0.004 which means that the value is smaller than 0.05, that is, motivation is accepted to influence employee performance. In addition, H4 shows a significant value of 0.002 which means that the value is smaller than 0.05, which means that H4 is accepted. The conclusion of this study is that the motivation variable influences employee performance, while work stress variables and compensation do not affect employee performance. Simultaneously work stress, motivation and compensation affect employee performance. Suggestions for this research are expected in future studies to add other variables such as work environment, competence, leadership style and work discipline to get different results.